Body Shaming pada Remaja Putri: Solusi Perundungan (Bullying) Berbasis Nilai-Nilai Islam - Arif Widodo; Hakiki, Nurul (Da'wah Faculty of UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
Body shaming is a type of bullying often carried out unconsciously by the community, starting from close friends, teachers, and even parents. Body shaming by making fun of someone's physical condition can harm victims and perpetrators. Therefore, this behavior needs to be addressed by implementing Islamic values. This research aims to find out the impact of body-shaming bullying on young girls and how Islamic values can overcome it. The method used is a literature review, which involved collecting 15 articles published in the last five years. The results were: 1. Body shaming is a form of bullying; structures of body shaming exist, such as fat shaming, thin shaming, hairy bodies, and skin color. An example is ridiculing and denouncing body shapes such as crooked, chubby, fat, short, black, and so on. 2. The impact of body shaming on young women affects them physically and psychologically. Victims of body shaming will feel ashamed and insecure, limit themselves, isolate themselves, have anorexia and body dysmorphic disorder, and can experience increased stress, resulting in suicide. 3. Body shaming is seen as disgraceful behavior from an Islamic perspective. This behavior is included in despicable morals (madmunah). 4. Implementing Islamic values can prevent and overcome body-shaming behavior for perpetrators and victims. Applying Islamic values requires cooperation from various parties, such as family, educators, the community, and the environment